POETICS OF DRAMATURGY OF IHOR KOSTETSKY - Семак, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article has the analysis of peculiarities of Ihor Kostetsky’s dramaturgy. The author singles out and characterizes the system of creative means of the writer that give an opportunity to speak about the influence of existential searching of the author on the inner form of the work.